Physics of Graphene - Aoki, Hideo; S. Dresselhaus, Mildred (NanoScience and Technology,, 2014)
This book provides a state of the art report of the knowledge accumulated in graphene research. The fascination with graphene has been growing very rapidly in recent years and the physics of graphene is now becoming one of the most interesting as well as the most fast-moving topics in condensed-matter physics. The Nobel prize in physics awarded in 2010 has given a tremendous impetus to this topic. The horizon of the physics of graphene is ever becoming wider, where physical concepts go hand in hand with advances in experimental techniques. Thus this book is expanding the interests to not only transport but optical and other properties for systems that include multilayer as well as monolayer graphene systems. The book comprises experimental and theoretical knowledge. The book is also accessable to graduate students.